THE ROLE OF FAECAL MICROBIOTA TRANSPLANTATION (FMT) IN THE TREATMENT OF OBESITY — A SYSTEMATIC REVIEW INCLUDING THE LATEST RESEARCH FROM 2020–2025 - Hanna Pietruszewska; Oliwia Sędziak; Natalia Kruszewska; Sabina Skrzynecka; Urszula Borucińska (International Journal of Innovative Technologies in Social Science, 2025)
FMT is a very promising, though still experimental, method of influencing the composition and functioning of the gut microbiota. In recent years, more and more research teams have been focusing on its potential in the treatment of obesity, type 2 diabetes, metabolic syndrome and lipid metabolism disorders. Publications show that FMT can lead to permanent changes in the recipient’s microbiome, including increased species diversity, an increase in the number of bacteria producing short-chain fatty acids, and modification of metabolic pathways related to glucose and lipid metabolism. The relationships between the gut microbiota and the functioning of the immune and nervous systems are also becoming better understood, opening up new therapeutic possibilities. The collection and critical analysis of clinical and experimental research results not only allows us to determine the safety and tolerance of this method, but also to indicate the directions in which future projects should be developed in order to fully assess its effectiveness in the long term. The aim of the study was to collect and organise the results of clinical trials on the use of faecal microbiota transplantation (FMT) in people with obesity or metabolic syndrome, to assess the impact of this method on metabolic parameters, and to analyse the current state of knowledge on the impact of FMT on weight loss, metabolic parameters and gut microbiome composition in individuals with obesity, in light of studies from 2020–2025, and to identify the mechanisms of action of faecal microbiota transplantation (FMT) and determine its therapeutic potential in the treatment of obesity based on the results of the above-mentioned studies. Ten randomised controlled trials comparing FMT with placebo or standard treatment were included in the analysis. It was found that faecal microbiota transplantation may have a beneficial effect on metabolic parameters such as insulin sensitivity and lipid profile, but its efficacy and durability require confirmation in longer, better-designed clinical trials.